Changes in some blood parameters, milk composition and yield of buffaloes (Bubalus bubalis) during the transition period. (4th August 2017) - Fiore, Enrico; Giambelluca, Sonia; Morgante, Massimo; Contiero, Barbara; Mazzotta, Elisa; Vecchio, Domenico; Vazzana, Irene; Rossi, Pasquale; Arfuso, Francesca; Piccione, Giuseppe; Gianesella, Matteo
Abstract: In this study changes in hematochemical parameters, milk composition and yield were investigated in buffaloes during the transition period. A total of 93 buffaloes 113.9 ± 8.03 months old and 535 ± 50 kg average body weight were used. Parity was recorded, blood samples were collected from 80 days pre‐partum until 70 days post‐partum; milk samples were collected from 5 days to 70 days post‐partum. On serum samples, the values of non‐esterified fatty acids, β‐hydroxybutyrate, glucose, cholesterol, triglycerides, aspartate aminotransferase, alanine aminotransferase, gamma‐glutamyltransferase, urea, total proteins were evaluated. On milk, percentage of fat, protein and lactose, along with the somatic cell count (SCC), milk yield and daily milk production (DMP) were assessed. The peripartum period significantly ( P  ≤ 0.01) influenced all studied parameters with the exception of glucose. Milk fat percentage showed decreasing trend from 10 until 40 days post‐partum; DMP significantly ( P  ≤ 0.01) increased from 1 day post‐partum until 40 days post‐partum. Milk yield significantly ( P  ≤ 0.01) decreased in animals over the sixth lactation. Our results confirmed the importance of transit period in buffaloes. Blood parameters and milk composition alterations are crucial to predict the energy balance status of buffaloes in order to improve their management and feed intake during the transition period.